Revealing well-educated millenials' purchase intention on halal cosmetics: The role of knowledge, religiosity, and attitude - Salsabilla Kurniawati; Rosa Prafitri Juniarti; Azizah Omar; Ahmad Ajib Ridlwan (Universitas Negeri Surabaya, 2023)
This study aimed to analyze and discuss the influence of knowledge, religiosity, and attitude on well-educated Muslim women Millenials’ interests in buying halal cosmetics in a state with a Muslim majority. The judgemental sampling technique was applied to take samples using an online questionnaire. Two hundred twenty-three respondents were collected, yet, only 210 well-educated Muslim women with minimum ages of 21 years old could participate. Data is analyzed using path analysis to see the correlation among variables. The result found that well-educated Muslim women Millenials had a positive interest in buying halal cosmetics. Besides any information about halal cosmetics products, their belief level on their religion significantly affected their attitude and interests in buying. It found that most of the respondents knew halal cosmetics from the internet through open questions. Although a state with a Muslim majority becomes the research location, many people still used cosmetics with no halal certificates. Therefore, marketers should advertise their halal products, mainly through digital media. This study focused on consumers' attitudes toward rapid-growth cosmetics products in Indonesia, and it referred to halal cosmetics. Also, this study focused on the millennials generation who had an age group with the most number. Therefore, it was necessary to put this issue into a marketing discussion.